RISK APPREHENSION AND INVESTMENT BEHAVIOUR OF SMALL INVESTORS - Simi B.S (MIRROR, 2018)
Investment is essential for the growth of individual as well the society. The quantum and quality of investment depends on the risk apprehension and behaviors of investors. This henomenon is true in every individual especially in sm ll investors. This study “Risk Apprehension and Investment Behaviour of Small Investors’ evaluates the attitude, behavior and risk Apprehension of small investors. The study uses the variable like amount of investment, time of investment, factors affecting investment decision etc